How to ensure effective government responses as COVID-19 spreads to rural areas - Kosec, Katrina; Ragasa, Catherine (International Food Policy Research Institute, 2022)
As COVID-19 began spreading globally in early 2020, it quickly went beyond major cities to affect rural areas in much of the world. In low-income countries, rural health systems have been overloaded and periodic lockdowns and other restrictions have driven down incomes. Governments have responded to the economic turmoil with an array of social protection programs, and through public health campaigns pushing both safe behaviors and vaccination and providing treatment. As our 2019 IFPRI Policy Brief shows, ensuring high-quality governance and provision of services in rural areas is critical for livelihoods and economic development — and thus central to COVID-19 policy responses.